Mutagenicity, antimutagenicity and tyrosinase inhibition activity of hydroglycol extracts from terminalia chiebula retzius, terminalia belerica roxb and rafflesia ke/Rimeijer - Wijittra Nittayajaiprom (2018)
© 2014, Advanced Research Journals. All rights reserved. The hydroglycolic extracts from Terminaiia chiebula Retzius, Termnnalia belerca Roxb and Rafflesia kerrii Meijer were investigated for total phenolic content (TPC), cytotoxicity, mutagenicity, antimutagenicity and antityrosinase for safety assessment as novel botanical-based cosmeceutical ingredients. These plant extracts showed TPC between 4.90 ± 0.02 and 112.40 ± 0.08 mg GAE g-1 of extract when using the Folin-Ciocalteu method. The cytotoxicity study revealed that the 50% cytotoxicity dose (CD50) towards normal mouse fibroblast L929 and mouse melanoma B16F10 cell lines was 5.43 ± 0.18 - 39.39 ± 0.14 mg mL-1 and 4.35 ± 0.33 - 58.23 ± 0.18 mg mL-1, respectively. In genotoxicity investigation, it was found that all extracts were not mutagenic at the concentrations up to 87.34 mg 0.1 mL-1 when tested with Salmonella typhhimuruum strains TA98 and TA100 in the presence and absence of metabolic activation (S9 microsomal fraction). The extracts were further tested for antimutagenic activity against 2-aminoanthracene (2-AA) and 2-(2-furyl)-3-(5-nitro-2-furyl) acrylamide (AF-2) which were used as the tested mutagens. Interestingly, all hydroglycolic extracts exhibited the inhibitory effect on the mutagenicity after being induced by 2AA and AF-2 in S. typhimurium strains TA98 and TA100 in the presence and absence of metabolic activation. All plant extracts were further investigated for tyrosinase inhibitory activity. Results showed that all extracts possessed tyrosinase inhibitory activity with 50% inhibitory concentration values (IC50) of 1.27 ± 0.49 - 39.96 ± 0.21 mg mL-1. Overall studies including their antimutagenicity and antityrosinase activities suggest that the hydroglycolic extracts of these three plants may be used as potential candidates for skin-care cosmeceutical ingredients.